A Cross‐sectional Study of the Association between Working Hours and Sleep Duration among the Japanese Working Population. Issue 4 (6th February 2014) - Ohtsu, Tadahiro; Kaneita, Yoshitaka; Aritake, Sayaka; Mishima, Kazuo; Uchiyama, Makoto; Akashiba, Tsuneto; Uchimura, Naohisa; Nakaji, Shigeyuki; Munezawa, Takeshi; Kokaze, Akatsuki; Ohida, Takashi
Abstract : A Cross‐sectional Study of the Association between Working Hours and Sleep Duration among the Japanese Working Population: Tadahiro OHTSU, et al . Department of Public Health, Showa University School of Medicine, Japan— Objectives: This study aimed to clarify the association between long working hours and short sleep duration among Japanese workers. Methods: We selected 4, 000 households from across Japan by stratified random sampling and conducted an interview survey of a total of 662 participants (372 men; 290 women) in November 2009. Logistic regression analyses were performed using "sleep duration <6 hours per day" as a dependent variable to examine the association between working hours/overtime hours and short sleep duration. Results: When male participants who worked for ≥7 but <9 hours per day were used as a reference, the odds ratio (OR) for short sleep duration in those who worked for ≥11 hours was 8.62 (95% confidence interval [CI]: 3.94−18.86). With regard to overtime hours among men, when participants without overtime were used as a reference, the OR for those whose period of overtime was ≥3 hours but <4 hours was 3.59 (95% CI: 1.42−9.08). For both men and women, those with long weekday working hours tended to have a short sleep duration during weekdays and holidays. Conclusions: It is essential to avoid working long hours in order to prevent short sleep duration.